1994
DOI: 10.1161/01.str.25.7.1481
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-alpha expression in ischemic neurons.

Abstract: Background and Purpose Tumor necrosis factor-a (TNF-a) is a cytokine with diverse proinflammatory actions, including endothelial leukocyte adhesion molecule expression. Since leukocytes infiltrate into ischemic brain lesions, the present study was conducted to examine whether TNF-a messenger RNA (mRNA) and peptide are expressed in the brain after experimental focal stroke and before leukocyte accumulation.Methods TNF-a mRNA and protein expression were monitored in the ischeraic and nonischemic cerebral cortex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
428
0
12

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 728 publications
(458 citation statements)
references
References 55 publications
18
428
0
12
Order By: Relevance
“…It has been previously demonstrated that astrocytes have the capacity to secrete TNF-α (Chung and Benveniste 1990) and that TNF-α colocalized with neurofilaments in the cerebral cortex (Liu et al 1994) in response to a variety of stimuli such as ischemia. Dipyridamole, blocking the increased expression of the cytokine TNF-α in astrocytes, may decrease the proinflammatory milieu associated with the ischemic insult.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously demonstrated that astrocytes have the capacity to secrete TNF-α (Chung and Benveniste 1990) and that TNF-α colocalized with neurofilaments in the cerebral cortex (Liu et al 1994) in response to a variety of stimuli such as ischemia. Dipyridamole, blocking the increased expression of the cytokine TNF-α in astrocytes, may decrease the proinflammatory milieu associated with the ischemic insult.…”
Section: Discussionmentioning
confidence: 99%
“…We tested the ability of Slit to modulate chemotaxis in the in vivo brain using two different proinflammatory stimuli: The cytokine TNFα (Carvalho-Tavares et al, 2000), and transient global ischemia, in which TNFα derived from resident cells (Liu et al, 1994;Gregersen et al, 2000;Botchkina et al, 1997;Uno et al, 1997;Feuerstein et al, 1998) and mediators of other inflammatory signaling cascades promote postischemic inflammation in the postcapillary venular system and in cerebral parenchyma. In both models, we found exogenously administered Slit to be potently effective in reducing cerebrovascular inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that TNF-a, which is expressed or released after ischemia (Liu et al, 1994), contributes to the damaging effects of this condition (for a review, see Shohami et al, 1999). However, additional evidences have demonstrated a direct, neuroprotective role of TNF-a (for a review, see Shohami et al, 1999).…”
Section: Discussionmentioning
confidence: 99%